Granulocyte-macrophage colony-stimulating factor activates the transcription of nuclear factor kappa B and induces the expression of nitric oxide synthase in a skin dendritic cell line. - Cruz, MT (2001)
Nitric oxide (NO) produced by skin dendritic cells and keratinocytes plays an important role in skin physiology, growth and remodelling. Nitric oxide is also involved in skin inflammatory processes and in modulating antigen presentation (either enhancing or suppressing it). In this study, we found that GM-CSF stimulates the expression of the inducible isoform of nitric oxide synthase (iNOS) in a fetal-skin-derived dendritic cell line (FSDC) and, consequently, increases the nitrite production from 11.9 +/- 3.2 micromol/L (basal level) to 26.9 +/- 4.2 micromol/L. Pyrrolidinedithiocarbamate (PDTC) inhibits nitrite production, with a half maximal inhibitory concentration (IC50) of 19.3 micromol/L and the iNOS protein expression in FSDC. In addition, western blot assays revealed that exposure of FSDC to GM-CSF induces the phosphorylation and degradation of the inhibitor of NF-kappaB (IkB), with subsequent translocation of the p50, p52 and RelB subunits of the transcription nuclear factor kappa B (NF-kappaB) from the cytosol to the nucleus. Electrophoretic mobility shift assays (EMSA) showed that FSDC exposure to GM-CSF activates the transcription factor NF-kappaB. Together, these results show that GM-CSF induces iNOS expression in skin dendritic cells by a mechanism involving activation of the NF-kappaB pathway.